The weight of the gavel: prison as a rite of passage - Green, Edward L. W. (Kansas State University, 2016)
This qualitative study draws from 54 interviews with "lifers" -- those serving 20 years or more -- from three correctional facilities across Kansas; it addresses the stark void in criminological literature about prison culture in the context of late-modern penality. This dissertation explores identity transformation of inmates serving a life sentence, proposing that incarceration represents a new rite of passage for 2.22 million citizens in the US. This inquiry utilizes the concept of liminality to capture the "betwixt and between" component of significant life transitions such as being handed a life sentence. Extending Jewkes' (2002) work on liminality, the study advances and supports the notion of a suspended liminality, an elongated vulnerability to one's sense of self, which, for those serving a long prison sentence, generally occurs during the first five years. Eventually, some lifers are able to rebuild social networks. The process of identity transition reflects an interstitial drift between suspended liminality and prisonization, contingent upon social support, sense of belonging, and forms of hope. Reconsidering the notion of a permanent "social death," this study provides evidence of a social purgatory, yielding a period of chaos and confusion in which the self is in turmoil, engaged in a battle to find meaning and purpose. The analysis employs group interviews, multiple on-site observations, field notes, and a night in solitary confinement; three inmates assisted in the interview design. This dissertation contributes a "thick description" of contemporary life in US prisons and transitions through long sentences that may present barriers to successful reentry.
Keywords: Prison; Identity; Liminality; Cultural; Criminology; Punishment